Evaluasi Jalan Tambang Untuk Meningkatkan Produksi dari Pit A 1 B Ke Evortable Finish Ore (EFO) Di PT Paramitha Persada Tama Blok Kerja PT Bintang Delapan Resources - Edo Febrinaldi; Yoszy Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. PT Paramitha Persada Tama is a laterite nickel mining company located in Boenaga Village, Lasolo Islands District, North Konawe Regency, Southeast Sulawesi Province. PT Paramitha Persada Tama has a Production IUP on the Boenaga block and an Exploration IUP on the Marombo block. PT Paramitha Persada Tama is a company engaged in nickel mining which is one of the job sites of PT. Bintang Eight Resources. PT Paramitha Persada Tama has a production target of 55,000 tons per month but the production achievement achieved is only 49,452.552 tons, so improvements are needed. From observations in the field, firstly, the geometry of the haul road is not ideal for hauling movements and is not safe for other road users. The minimum width of the road that can be traversed by DT HINO 500 Fm 250 JD is 8.6 m on straight roads and 15 m on bends and the absence of safety bombs for some road points. Therefore, there is a need for a technical study of haul road geometry to optimize the cycle time of the conveyance. Several aspects that need to be studied in the mining haul road area are the width of the straight road, the width of the bend road, grade, superelevation, and cross slope. After repairs were made, the initial production output was 49,452.552 tons, after improving productivity, it became 55,743.336 tons, so that the production target of 55,000 tons was achieved.Keywords: production, road geometry, safety berm